Combatir la violencia contra las mujeres políticas:: la influencia internacional de la pionera legislación boliviana - Castaño, Pablo (Investigaciones Feministas, 2021)
Introduction. Violence against women in politics (VAWP) is a specific form of gender-based violence that is receiving growing attention from research, because it threatens the progress made in women’s political representation. However, there are few works on how to design legislation against VAWP. Objectives. This article contributes to filling this gap by analysing how the Bolivian legislation influenced norms of VAWP drafted and passed by other countries and international organisations in Latin America, the country where more efforts of this kind have taken place – the 243/2012 Bolivian Law on Political Violence and Harassment against Women was the first law on VAWP in the world –. Methodology. The research draws on qualitative content analysis of the legislation and semi-structured interviews with Bolivian women’s activists, officials and MPs. Results, conclusions and discussion. I argue that four specific features of the Bolivian legislation have had a major influence on other norms on VAWP: (i) a wide and detailed definition of VAWP; (ii) the attribution to the electoral organ of competences to prevent VAWP; (iii) the establishment of political parties’ responsibilities; (iv) the (incomplete) adoption of an intersectional perspective.